STRATEGI PENGHIDUPAN RUMAHTANGGA MISKIN PERDESAAN (KASUS DI TIGA DESA KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA) - , Muhammad Arif Fahrudin Alfana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this research is to describe the profile of poor rural households, explain the causes of poverty, explain the livelihood strategies, explaining the correlation between the profile and the choice of livelihood strategies households and compares the differences livelihood strategies n three study areas. Data collection is conducted by combining two methods: qualitative and quantitative. Quantitative methods of data survey conducted by the agencies and distributed questionnaires to 323 respondents with a proportional random sampling. Qualitative data collection is conducter by a case study in households with in-depth interviews. Data analysis was performed by descriptive and comparative analysis by comparing the three villages in the study area The conclusion of this research is show that the poor in the three study regions implement various livelihood strategies for survival everyday. Amounting to 68.73 percent of poor households use survival strategies while 28.27 percent using consolidation strategy and 3.10 using accumulation strategy. Survival strategies that do the poor, among others, by utilizing dasawisma, do subsistence business, optimizing the use of family labor, become a labor cattle, looking for a second job and take advantage of government aid. Konsolidation strategies that do by improve assets, looking for the second job, utilizing cooperation and bank, and optimizing son. Accumulation strategies that do by improve assets such as livestock. The relationship between livelihood strategies in the areas of research related to factors such as land ownership, education, income received, ownership of assets and ownership of livestock that have a positive relationship.Ageing and education have negative relationship